2017
DOI: 10.1186/s13024-017-0221-9
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic profiling of neuronal mitochondria reveals modulators of synaptic architecture

Abstract: BackgroundNeurons are highly polarized cells consisting of three distinct functional domains: the cell body (and associated dendrites), the axon and the synapse. Previously, it was believed that the clinical phenotypes of neurodegenerative diseases were caused by the loss of entire neurons, however it has recently become apparent that these neuronal sub-compartments can degenerate independently, with synapses being particularly vulnerable to a broad range of stimuli. Whilst the properties governing the differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 42 publications
0
52
0
Order By: Relevance
“…Synaptic preparations were prepared and quality control for post-mortem protein degradation were confirmed as previously described 12, 13, 14 (Supplementary Figure 1 for example total protein stains and western blotting). Any synaptoneurosome preparations containing nuclear histone protein were discarded and fresh preparations made from the same case.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Synaptic preparations were prepared and quality control for post-mortem protein degradation were confirmed as previously described 12, 13, 14 (Supplementary Figure 1 for example total protein stains and western blotting). Any synaptoneurosome preparations containing nuclear histone protein were discarded and fresh preparations made from the same case.…”
Section: Resultsmentioning
confidence: 99%
“…Having confirmed that the extracted protein is of appropriate quality, we then applied a comprehensive workflow to enable us to assess (at the protein level) the relative contribution of both regional vulnerability and APOE variants as a risk factors to AD pathogenesis (Figure 1C, Figure 2) 12, 13 . We performed a complex 8-plex TMT LC-MS/MS analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data set is then visualized as nodes (proteins) that are connected to each other in a network based on their expression levels (edges). This data set can further be subdivided into discreet "clusters" based on a Markov Clustering Algorithm (MCL), thus segregating data in an unbiased manner as previously described [66][67][68].…”
Section: Biolayoutexpress3dmentioning
confidence: 99%